2010
DOI: 10.1177/0146167210372505
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving Your Group’s Future to Be in Jeopardy: Extinction Threat Induces Collective Angst and the Desire to Strengthen the Ingroup

Abstract: Collective angst reflects concern about the ingroup's future vitality. In four studies, the authors examined the impact of ingroup extinction threat on the experience of collective angst. In Study 1, collective angst was elicited in response to a physical or symbolic ingroup extinction threat compared to a no-threat control group. In Study 2, the extent to which French Canadians expressed collective angst because of the perceived extinction threat posed by English Canada predicted desire to engage in ingroup s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
260
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(279 citation statements)
references
References 44 publications
19
260
0
Order By: Relevance
“…Importantly, group-level emotions function to regulate group-relevant or collective behavior (Maitner, Mackie, & Smith, 2006;van Zomeren, Leach, & Spears, 2012), rather than individual behavior (Carver, 2015). In the case of collective angst, behavior is directed towards attempts to secure the future vitality of the in-group.Although there are individual differences in the extent to which group members feel collective angst (Jetten & Wohl, 2012;Wohl, Porat, & Halperin, 2016), appraising a perceived threat to the group's future vitality will elicit this group-based emotion (Lucas et al, 2014;Mashuri & Zaduqisti, 2015;Mols & Jetten, 2014;Wohl, King, & Taylor, 2014;Wohl et al, 2010). This emotional reaction is distinct from other related group-based emotional reactions, such as collective fear (Wohl & Branscombe, 2009;Wohl et al, 2010).…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…Importantly, group-level emotions function to regulate group-relevant or collective behavior (Maitner, Mackie, & Smith, 2006;van Zomeren, Leach, & Spears, 2012), rather than individual behavior (Carver, 2015). In the case of collective angst, behavior is directed towards attempts to secure the future vitality of the in-group.Although there are individual differences in the extent to which group members feel collective angst (Jetten & Wohl, 2012;Wohl, Porat, & Halperin, 2016), appraising a perceived threat to the group's future vitality will elicit this group-based emotion (Lucas et al, 2014;Mashuri & Zaduqisti, 2015;Mols & Jetten, 2014;Wohl, King, & Taylor, 2014;Wohl et al, 2010). This emotional reaction is distinct from other related group-based emotional reactions, such as collective fear (Wohl & Branscombe, 2009;Wohl et al, 2010).…”
mentioning
confidence: 98%
“…Yet, social groups are not static; they change-a reality that, when salient, is often perceived as a threat to one's social identity (Riek, Mania, & Gaertner, 2006) and thus produces distress among group members (Chandler & Lalonde, 1998;Lampinen, Odegard, & Leding, 2004). This distress may manifest in collective angst-a group-based emotion that reflects concern for the future vitality of the in-group (Jetten & Wohl, 2012;Wohl, Branscombe, & Reysen, 2010).Importantly, collective angst originates from perceived extinction threats to one's in-group. These threats may take the form of realistic extinction threats posed by adversarial out-groups (Halperin, Porat, & Wohl, 2013;Wohl et al, 2010) but may also take the form of symbolic threats to the group's social identity (e.g., loss of cultural vitality; Wohl, Giguère, Branscombe, & McVicar, 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These forms of insecurities have been documented by researchers. For example, Wohl, Branscombe, and Reysen (2010), found that French Canadians who feel that their group's existence is being threatened by English Canada display group-based anxiety, referred to as collective angst.…”
Section: Discussionmentioning
confidence: 99%